Effects of Communication Skills in the Physical Education on Enjoyment and Involvement among High-School Students - Forough ShafaeianFard; Mohammad Karimakhani; Ali Abedini; Elay Janamoo Berenj Abadi (Journal of Modern Psychology, 2023)
Communication is associated to the effectiveness and efficiency of any sports team function due to its informative, motivational and evaluative role. However, the effects of communication skills within the physical education context are rarely investigated. Hence, the aim of this study was to investigate the effects of communication skills in the physical education on enjoyment and involvement of high school students. It was hypothesized that communication skills within the physical education class have positive effects on enjoyment and involvement of high-school students. The method used in this study was a structural equation modelling. The participants included 384 adolescents age 16 to 18 years old (mean 16.96±0.57 years old) who attended in regular high-schools. Teacher Communication Behavior Questionnaire (TCBQ) and Fragebogens zur Erfassung von Freude am Schulsport im Jugendalter (FEFS-J), and Student Engagement Instrument (SCI) were used for assessing communication skills, enjoyment, and involvement. To analyze data, we used Pearson correlation test and structural equation modeling. Results showed that communication skills had significant effects on enjoyment (T=4.182) and involvement (T=6.082). In addition, enjoyment had significant effects on involvement (T=3.291). Results of evaluating fitness of good showed that our model has a good fit (GOF=0.93). Communication skills are very important for engagement and learning of students.